Multiframe particle tracking in intravital imaging defining Lagrangian coordinates in the microcirculation - Ravnic, Dino J (BioTechniques, 2006)
The cellular composition of the microcirculation creates blood flow that can be unsteady and nonuniform. To obtain information about nonuniform cellular trajectories, we describe in vivo imaging techniques that provide both detailed tracking of individual particles as well as an approach to simultaneous multicolor particle tracking. Particularly relevant to biologic systems, Lagrangian methods provide information about the fate of individual particles and flow in the system